PENGARUH BIOCHAR SEKAM PADI DAN KOMPOS KOTORAN AYAM TERHADAP PERTUMBUHAN BIBIT KELAPA SAWIT (Elaeis guineensis Jacq.) PADA TANAH ULTISOL - Nurhaja Nurhaja; Beny Setiawan; Syawaldi Syawaldi (Politeknik Negeri Ketapang, 2025)
Ultisol media are physically relatively infertile and low in organic matter content. This study aims to determine the effect of rice husk biocharand chicken manure compost on the growth of oil palm seedlings in ultisol soil media. The study was conducted from April to June 2025 at the experimental farm on Jalan Gusti Mesir, Medan Jaya Village, Simpang Hilir Subdistrict, Kayong Utara Regency. The experiment used a factorial RAL design consisting of two treatment factors. The first factor was rice husk biochar, which consisted of 3 levels, namely B0 = without biochar, B1 = 75 g/polybag, and B2 = 150 g/polybag. The second factor was chicken manure compost with 3 levels, namely K0 = without compost, K1 = 375 g/polybag, and K2 = 450 g/polybag. The observation parameters included plant height, stem diameter, number of leaves, root length, root volume, and soil pH. The data were analyzed using analysis of variance, and if there was a significant effect, it was followed by Duncan's Multiple Range Test (DMRT) at a 5% level. The results showed that the application of rice husk biocharand chicken manure compost had a significant effect on oil palm seedling growth. The best dose was obtained from the combination of 75 g of biochar and 375 g/polybag of compost, which significantly increased plant height, stem diameter, number of leaves, root length, root volume, and soil pH.